1980
DOI: 10.1002/ana.410070112
|View full text |Cite
|
Sign up to set email alerts
|

The carcinomatous neuromyopathy of oat cell lung cancer

Abstract: A prospective controlled clinical-neurophysiological-pathological study of 71 patients with oat cell carcinoma of the lung revealed no increased incidence of peripheral neuropathy at the initial stages of illness. All patients developed neuropathy by the time they had lost 15% of their body weight, but the neuropathy was less severe than in 20 age-matched alcoholic patients with an equal degree of weight loss. The weight loss and peripheral neuropathy progressed with atrophy of type II (adenosine triphosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Other tumors include small cell carcinomas of the prostate and cervix, lymphomas, and adenocarcinomas. The prevalence of LEMS in patients with SCLC is estimated to be around 3% [87,89]. Clinically and serologically, the 30% without identifiable tumors are indistinguishable from the paraneoplastic LEMS patients, although LEMS may have a more progressive course in patients with SCLC [85].…”
Section: Underlying Tumormentioning
confidence: 99%
“…Other tumors include small cell carcinomas of the prostate and cervix, lymphomas, and adenocarcinomas. The prevalence of LEMS in patients with SCLC is estimated to be around 3% [87,89]. Clinically and serologically, the 30% without identifiable tumors are indistinguishable from the paraneoplastic LEMS patients, although LEMS may have a more progressive course in patients with SCLC [85].…”
Section: Underlying Tumormentioning
confidence: 99%
“…variety of neurodegenerative diseases are known to be associated with different types of cancer, even though the tumor and its metastases have not invaded the nervous system (Brain and Norris, 1965;Brain and Wilkinson, 1965;Brain et al, 1951;Croft and Wilkinson, 1963;Denny-Brown, 1948;Hawley et al, 1980;Henson and Urich, 1982;Minna and Bunn, 1982;Norris, 1972). These "remote effects" of cancer, or paraneoplastic syndromes, are of undetermined etiology, although some studies have implicated viral, hormonal or toxic origins (Brain and Norris, 1965;Hawley et al, 1980;Sawyer et al, 1976;Schold et al, 1979).…”
mentioning
confidence: 99%
“…These "remote effects" of cancer, or paraneoplastic syndromes, are of undetermined etiology, although some studies have implicated viral, hormonal or toxic origins (Brain and Norris, 1965;Hawley et al, 1980;Sawyer et al, 1976;Schold et al, 1979). Alternatively, these degenerative diseases may stem from an autoimmune response that is directed towards antigens or epitopes found in both the tumor and specific neurons (Anderson et al, 1988;Keltner et al, 1983;Kornguth et al, 1982).…”
mentioning
confidence: 99%
“…We did not think that our patient had paraneoplastic cerebellar degeneration secondary to SCLC. Unlike patients with gynecological tumors, Erlington et al [5] (150 patients) and Hawley et al [6] (71 patients) reported no cerebellar syndrome at presentation in patients with SCLC.…”
Section: Discussionmentioning
confidence: 99%